A Social Development Assessment Scale for Mexican Children - Rocío Aguiar Sierra; Pedro Antonio Sánchez Escobedo; David J. Satterly (Universidad Autónoma de Baja California, 2005)
This work described the design of an instrument able to measure social development for Mexican children and the process of the establishment of its psychometric properties. Theoretical aspects considered for its construction and the process of validating forms for parents and teachers are described in a three stage processes that resulted in a final version of the Social Development Scale that measures, disruptive behavior, social interaction, cooperation, acceptance and attachment as core dimensions associated with the concept of social competence. The importance of assessing social development and competence for education, children rearing and general well being are analyzed and discussed.